Le vie chirurgiche di accesso: il pilone tibiale - Zottola, V.; Cremona, M.; Bonelli, C.; Foti, A.; Consonni, O. (Lo Scalpello - Journal, 2018)
SURGICAL APPROACHES: TIBIAL PILON Tibial pilon fractures represent a noteworthy surgical challenge. Usually caused by high-energy injuries, they are often burdened by frequent complications, in particular concerning soft-tissue healing. The literature reports several surgical approaches, some fracture-specific, others more extensile, to allow for an easier reduction and fixation of the whole articular surface. Thus, an accurate preoperative planning and a skilled surgeon play a primary role in the management of these injuries.